Explicando a contribuição do número de aplicações de fungicidas foliares na produtividade de lavouras de soja - Tura, Enrico Fleck (2023)
Disease control in soybeans in Brazil starts from the yield gap (currently the yield gap is 2400 kg ha-¹), it also increases production costs due to the need for input applications (foliar fungicides). Thus, adjusting the number of fungicide applications in fields will result in higher yields and/or lower production costs, which will increase the profitability of the intervention. Therefore, understanding the interaction with other management and environmental factors is critical to optimize resource use and reduce yield losses. In this sense, the objective of this work was to relate the number of foliar fungicide applications to field yield as a function of biophysical and management factors, in order to quantify the impact of foliar fungicide management on soybean crops in southern Brazil. To this end, we relate the number of foliar fungicide applications to field yield. We relate water-limited yield potential to the number of fungicide applications and field yield and establish a relationship between the relative maturity group of cultivars, productivity, and the number of foliar fungicide applications. The results show that the maximum yield for a fungicide application is 599.6 kg ha-1. Crops that receive a greater number (3-5) of fungicide applications have a 50% or greater chance of producing above average yields. The optimal number of foliar fungicide applications was influenced by the water-limited potential of the crop, with fields with greater water-limited productivity potential and cultivars with a lower GMR (< 5.8) responding better to a greater number of fungicide applications foliar. It was found that the maximum response to foliar fungicide application is 599.8 kg ha-1 for each application. Water-limited yield potential must be considered when determining the number of applications. Early-cycle varieties require a greater number of foliar fungicide applications.